1976
DOI: 10.1084/jem.143.6.1475
|View full text |Cite
|
Sign up to set email alerts
|

A genetic polymorphism in the constant region of rabbit b4 kappa chains.

Abstract: Much of what is known about the number and arrangement of genes encoding immunoglobulins, and the mechanisms involved in their selective expression, derives from studies involving allotypes. Rabbit allotypes have figured prominently in these studies particularly because they are found in almost every region of the immunoglobulin molecule. Amino acid sequence studies on rabbit allotypes of group a in the Vs region and group b in the C~ region have revealed an unusual degree of structural complexity within these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Such bias was not found in the latest generation, which included barb 4v rabbits. Quantitative analysis for b4 v placed this allotype in the group b allotype 'pecking order' (Dubiski 1972) at approximately the same level as b5, a result consistent with quantitative sequence data for b4b4 v rabbits reported earlier (Sogn and Kindt 1976).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Such bias was not found in the latest generation, which included barb 4v rabbits. Quantitative analysis for b4 v placed this allotype in the group b allotype 'pecking order' (Dubiski 1972) at approximately the same level as b5, a result consistent with quantitative sequence data for b4b4 v rabbits reported earlier (Sogn and Kindt 1976).…”
Section: Introductionsupporting
confidence: 81%
“…Chemical typing of b4 v was carried out as previously described (Sogn and Kindt 1976), by acid cleavage of mildly reduced and alkylated, succinylated L chains, followed by fifteen steps of automated Edman degradation using a Beckman Model 890C Sequencer. Two features of this assay procedure were examined in greater detail for the purposes of the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sogn and Kindt have described a b4ar, which differs from the H sequence by two residues (35). Breeding studies suggest that H and b4ar could correspond to alternative forms of a H chain gene at a single genetic locus.…”
Section: Discussionmentioning
confidence: 99%
“…The extraordinary number of differences in amino acid sequence between molecules bearing the various group a allotypic markers in the rabbit is well established. In addition, extensive sequence differences exist between b4, b6, and b9 constant regions of rabbit light chains (27)(28)(29)(30)(31). Recently, Gutman et al (32) have demonstrated that the kappa allotypes in the rat have multiple amino acid differences in the constant region.…”
Section: Discussionmentioning
confidence: 99%